2018
DOI: 10.1016/j.scienta.2018.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and core collection of Malus × domestica in northwestern Spain, Portugal and the Canary Islands by SSRs

Abstract: The domesticated apple (Malus × domestica Borkh.) is one of the most relevant cultivated fruit crops worldwide, in particular in temperate zones, and the fourth most economically important. In order to avoid loss of genetic diversity, germplasm banks have been established to conserve proper genetic diversity, among them we have evaluated five that covers western Iberian Peninsula (the one from Galicia and three from northern to southern Portugal) and Canary Islands.A total of 634 accessions composed of old and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
6
24
1
Order By: Relevance
“…Both NJ and STRUCTURE analyses showed a close relationship between La Palma and Spain mainland samples, which suggested the main origin of La Palma samples from the Iberian Peninsula. Similar results were obtained for other fruit tree species for which genetic diversity in La Palma was studied and compared to that in Spain, like almond [50], apple [51], chestnut [52], apple [53], or grapevine [54]. The rest of the accessions from La Palma that grouped in other clusters could be due to more recent plant introductions.…”
Section: Genetic Structuresupporting
confidence: 76%
“…Both NJ and STRUCTURE analyses showed a close relationship between La Palma and Spain mainland samples, which suggested the main origin of La Palma samples from the Iberian Peninsula. Similar results were obtained for other fruit tree species for which genetic diversity in La Palma was studied and compared to that in Spain, like almond [50], apple [51], chestnut [52], apple [53], or grapevine [54]. The rest of the accessions from La Palma that grouped in other clusters could be due to more recent plant introductions.…”
Section: Genetic Structuresupporting
confidence: 76%
“…Our results showed that a relatively few accessions were required to represent the whole genetic diversity with the minimum redundancy, probably due to the high heterozygosity of Vitis species [ 49 ]. Similar outcomes have been reported in Malus [ 50 ], which exhibits high levels of heterozygosity as well, whereas more individuals were needed in M. truncatula [ 51 ] that is characterized by lower allelic heterozygosity.…”
Section: Discussionsupporting
confidence: 82%
“…Principal coordinates analysis was unable to distinguish between the groupings and this was in line with a very low mean value for F ST (0.0035 P < 0.0001) between the two sets. Much larger, but still relatively low values for F ST have been reported for the analysis of local collections from Spain (0.057 ≤ F ST ≤ 0.12) (Pereira-Lorenzo et al 2007;Pereira-Lorenzo et al 2018;Pereira-Lorenzo et al 2008;Pereira-Lorenzo et al 2017), Bosnia and Herzegovina (F ST = 0.06) (Gasi et al 2010), Portugal (F ST = 0.074) (Ferreira et al 2016), and France (F ST = 0.048 [old cider cultivars] F ST = 0.031 [old dessert cultivars]) (Lassois et al 2016) when compared against sets of more modern international and commercial cultivars and for the comparison of local material from different European regions (0.015 ≤ F ST ≤ 0.042) (Urrestarazu et al 2016). Differing results have been found from studies in Italy where F ST values of 0.056 and 0.147 have been reported (Liang et al 2015;Marconi et al 2018), the higher value being specific to Central Italian local material and being generated after identifying groups by Bayesian analysis and removing the admixed accessions.…”
Section: Identification Of Wider Diversity (With Local Value)mentioning
confidence: 90%
“…Early studies (Hokanson et al 1998) established that the technology was able to differentiate material in collections. Numerous subsequent studies have utilised SSR markers to screen collections for duplication and diversity (Ferreira et al 2016;Garkava-Gustavsson et al 2008, 2013Gasi et al 2016;Gasi et al 2010;Gharghani et al 2009;Gross et al 2014Gross et al , 2012Guarino et al 2006;Marconi et al 2018;Patzak et al 2012;Pereira-Lorenzo et al 2007;Pereira-Lorenzo et al 2017;Testolin et al 2019;van Treuren et al 2010) and to identify core collections and subsets (Kim et al 2019;Lassois et al 2016;Liang et al 2015;Pereira-Lorenzo et al 2018), mostly on a national basis. Further studies have used the technology to examine parentage in pedigreed material (Cabe et al 2005;Evans et al 2011;Kitahara et al 2005;Lassois et al 2016;Moriya et al 2011;Salvi et al 2014) and compare the genetic diversity held across larger regions such as Europe (Urrestarazu et al 2016).…”
Section: Introductionmentioning
confidence: 99%